Elaboración de un matriz de solución direccionada a la mitigación de los efectos mecánicos y químicos a partir del estudio de las fallas que presentan las sartas de perforación de Estrella International Energy Services (2018)
The present work was carried out a design of a solution matrix of solutions of the failures presented during 10 years of work of the drillinstrings of Estrella International Energy Services, with pipe of grade S-135 OD of 5 ", Therefore, an evaluation is carried out in Quifa and Caño Limón Field, located in the Eastern Plains Basin and Purification Field located in the Upper Magdalena Valley Basin. This study was carried out from the Pareto theory for the selection of the most recurrent faults and / or damages, with a traceability study of the E707, E1225 and E2029 RIG, number of wells and feet drilled by each, taking into account counts the traceability of the pipeline throughout the analysis period. The selection of the faults contains important information to perform the laboratory tests of the samples of the drilling fluid taken in each of the fields to analyze chemically, in order to find chemical compounds that can generate chemical faults in the pipes. In addition, drilling conditions and parameters were evaluated mechanically, as well as design and working conditions, type of training, environmental conditions and storage. The solution matrix has alternatives and changes in the care and use of the pipeline, as well as improvements in good drilling practices and all that this entails.